Розробка біонічного протезу руки з використанням м’язового сенсору - Шевченко, А. Г. (ХНУРЕ, 2021)
The given work is devoted to the bionic prosthesis of an arm, built with help of a muscle sensor. It is able to accept muscle signals and grabbing various objects as well as transfer different loads till 5 kilograms. This was developed with the purpose to help disabled people with routine life.
Keywords: біонічний протез руки; м’язовий сенсор; біонічне протезування